2022
DOI: 10.1109/access.2022.3197225
|View full text |Cite
|
Sign up to set email alerts
|

Online Recruitment Fraud Detection: A Study on Contextual Features in Australian Job Industries

Abstract: The purpose of this study is to investigate the effects of contextual features on automatic detection accuracy of online recruitment frauds in Australian job market. In addition, the study aims to unearth the significance of localisation of such approaches. The study first generates a dataset based on a local and semi-structured advertising platform in Australia. The labelled dataset is then used to train a learning model on several content-based and contextual features. The existence of advertising body in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A report submitted by Ghosh et al (2021) developed prediction models by training several classifiers for detecting online recruitment fraud and concluded that voting was the most accurate model, with an accuracy of 95.34%. The study of Mahbub & Pardede (2018) proposed a novel approach of adding contextual features to increase the accuracy of the detection model for identifying online recruitment fraud. A study conducted by Zuhair, Selmat & Salleh (2015) used several features of selection techniques for building reliable models based on the subset of features and concluded that the accuracy of the phishing detection model was highest among the examined models.…”
Section: Related Workmentioning
confidence: 99%
“…A report submitted by Ghosh et al (2021) developed prediction models by training several classifiers for detecting online recruitment fraud and concluded that voting was the most accurate model, with an accuracy of 95.34%. The study of Mahbub & Pardede (2018) proposed a novel approach of adding contextual features to increase the accuracy of the detection model for identifying online recruitment fraud. A study conducted by Zuhair, Selmat & Salleh (2015) used several features of selection techniques for building reliable models based on the subset of features and concluded that the accuracy of the phishing detection model was highest among the examined models.…”
Section: Related Workmentioning
confidence: 99%
“…One of the primary channels for these fraudsters is social networking platforms, and another is online recruitment portals, where a job advertisement can be easily deceived into believing it is genuine. In fact, it is a forgery intended to defraud desperate job searchers (Mahbub et al, 2022). A secondary analysis of the 2014 U.S. "Caught in the Scammers' Net," a national survey of online victimization (N = 1,539), reveals that individuals with low self-control and those who engage in online activities are more inclined to disclose personal information online.…”
Section: Figure 02: Common Social Media Platforms For Cybercrimes Vic...mentioning
confidence: 99%
“…Online recruitment has now become the top choice for employer companies to recruit talents, and its scale is still expanding over the years compared with the conventional job fairs hold by urban public employment service agencies [1][2][3][4][5][6][7][8]. Affected by economic situations and the increasing number of college graduates, young people are facing greater employment pressure as the employer companies are posing higher requirements for talents [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%